Meningkatkan Hasil Belajar Shooting Bola Basket melalui Metode Pembelajaran Teaching at the Right Level (TaRL) pada Siswa Kelas X-3 SMAN 3 Jombang Tahun pelajaran 2022-2023 - Aulia Rahman (Journal on Education, 2023)
Education aims to prepare future generations of the nation who have three main competencies, namely character, critical thinking, being able to solve problems by increasing literacy and numeracy skills. School as a formal institution in the education system is inseparable from efforts to improve students' learning achievement. Research objectives The purpose of this research is "Improve Basketball Shooting Ability Through the Teaching at the Right Level (TaRL) Learning Method in Class X Students of SMAN 3 Jombang Academic Year 2022-2023". This type of research is Classroom Action Research (CAR). The subjects of this study were students of class X-3 of SMAN 3 Jombang in the 2022/2023 school year with a total of 20 students consisting of 12 boys and 22 girls. This Classroom Action Research (CAR) was conducted at SMAN 3 Jombang in February-May 2023 from cycle 1 to the end, namely cycle 2. In this study, tests were used as a means of collecting data. There are 2 tests used, namely: a basic shooting technique test and a shooting test according to Lethen and STO. Based on the results of the research and discussion in this study it can be concluded that by giving the Teaching at the Right Level (TaRL) learning method to the learning outcomes of shooting basketball for class X-3 students at SMAN 3 Jombang. In the pre-cycle there were 21 students who had completed with a completeness percentage of 61.76% and 13 students who had not completed with a completeness percentage of 38.24. Whereas in cycle 1 there were 25 students who had completed with a completeness percentage of 73.53% and 9 students who had not completed with a completeness percentage of 26.47%. In cycle 2 there were 30 students who completed with a percentage of 88.24% and 4 students who had not completed with a percentage of 11.76% completeness. From the explanation above, it can be proven that the use of the Teaching at the Right Level (TaRL) learning method on the learning outcomes of shooting basketball for class X-3 students at SMAN 3 Jombang.